Mutational Analysis of Agxt in Tunisian Population with Primary Hyperoxaluria Type 1. (9th December 2016) - M'dimegh, Saoussen; Omezzine, Asma; M'barek, Ibtihel; Moussa, Amira; Mabrouk, Sameh; Kaarout, Hayet; Souche, Geneviéve; Chemli, Jalel; Aloui, Sabra; Aquaviva‐Bourdain, Cécile; Achour, Abdellatif; Abroug, Saoussen; et al.
Summary: Background: Primary hyperoxaluria type 1 (PH1) is an autosomal recessive metabolic disorder caused by inherited mutations in the AGXT gene encoding liver peroxisomal alanine:glyoxylate aminotransferase (AGT). PH1 is a clinically and genetically heterogeneous disorder. The aim of our study was to analyze and characterize the mutational spectrum of PH1 in Tunisian patients. Materials and Methods: Molecular studies of 146 Tunisian patients suspected with PH were performed by PCR/Restriction fragment length polymorphism (RFLP) to detect seven mutations described as the most common. Direct sequencing for the 11 exons was performed in patients in whom any mutation was not identified. Results: The genetic diagnosis of PH1 was confirmed in 62.3% of patients. The first molecular approach based on PCR/restriction enzyme test was positive in 37.6% of patients, whereas the second molecular approach based on whole gene sequencing was successful in 24% of cases. Twelve pathogenic mutations were detected in our cohort. Two mutations were novel, and five were detected for the first time in Tunisians. The three most frequent mutations were p.Ile244Thr, p.Gly190Arg, and c.33dupC, with a frequency of 43.4%, 21.4%, and 13.1%, respectively. Conclusion: The two novel mutations detected in our study extend the spectrum of known AGXT gene mutations. The screen for the mutations identified in this study can provide a useful, cost‐effective, and first‐line investigation in Tunisian PH1 patients.